Tingkat keberhasilan Inseminasi Buatan (IB) menggunakan semen beku hasil sexing pada Sapi Persilangan Ongole - Ali mahfud; Trinil Susilawati; Aulia Puspita Anugra Yekti; Kuswati Kuswati (Faculty of Animal Science, Universitas Brawijaya, 2019)
The purpose of artificial insemination using sexing semen was to obtain the calf according to the expected sex. This study aimed to determine the success of artificial insemination in non-sexing and sexing of frozen semen. The materials used in this research were 77 non-sexing artificial insemination acceptor cows and 77 sexing artificial insemination acceptor cows with double dose treatment. The method used in this study was experimental field experiment with the research treatment: P0 = frozen non-sexing semen straw and P1 = frozen semen of spermatozoa Y by sexing method using Percoll Density Gradient Centrifugation (SGDP) produced by Balai Besar Inseminasi Buatan (BBIB) Singosari. The variables of this study were Non Return Rate (NRR), Service Per Conception (S/C) and Conception Rate (CR). The data obtained were analyzed descriptively. The results of the study in each non-sexing and sexing artificial insemination treatment were: the percentage of NRR 1 were 90.91% and 77.92%, followed by NRR 2 with 88.31% and 76.62%, the pregnancy percentage were 84.42% and 75.33%, and the CR values were 79.22% and 57.14%. The conclusion of this study was artificial insemination using frozen non-sexing semen had a higher success rate compared to artificial insemination using frozen sexing semen.